The Effect of STEM Project Based Learning on Self-Efficacy among High-School Physics Students - Samsudin, Mohd Ali; Jamali, Seyedh Mahboobeh; Zain, Ahmad Nurulazam Md; Ale Ebrahim, Nader (2020)
Science, Technology, Engineering and Mathematics (STEM) Project-Based Learning (PjBL) is increase effectiveness, create meaningful learning and influence student attitudes in future career pursuit. There are several studies in the literature reporting different aspects of STEM into a PjBL pedagogy. However, the effect of implementing STEM PjBL in terms of improving students’ skills in self-efficacy levels in physics mechanics at high school level has not been demonstrated as expected in the previous literature. This study followed a quasi-experimental research method. Bandura’s social cognitive theory is used to assess and compare the effect of STEM PjBL with conventional teaching method on students’ self-efficacy level in learning physics among over 100 high school students. The result illustrated that STEM PjBL improve students’ self-efficacy to solve physics problem. Also, the study proposes a guideline for future research.